(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
Stone matrix asphalt (SMA) was initially developed in Germany in the 1960s and has since proven to offer numerous benefits in road surfacing. It provides enhanced resistance to permanent deformation, improved durability, longer service life, reduced ageing effects, high resistance to cracking, fatigue, and wear, improved skid resistance, and noise reduction. SMA is a gap-graded mixture of aggregates that maximizes the asphalt-cement content and incorporates coarse aggregate fractions. Its stability and resistance to rutting rely on the interlocking contact between aggregates, while the presence of a rich mortar binder contributes to its durability. To further enhance the performance of SMA, a naturally available and cost-effective stabilizer, namely bamboo fiber, has been used. Bamboo fiber is a cellulose fiber extracted from bamboo stems, possessing high strength in the fiber direction, excellent tensile, flexural, and impact strength, and thinness suitable for stabilization purposes. It is durable, exhibits tenacity, and offers good stability. This study explores the suitability of bamboo fiber in enhancing the stability and flow characteristics of Stone Matrix Asphalt Mixes, aiming to improve the overall performance of the mixture.